Neolithic pottery and the biomolecular archaeology of lipids - Budja, Mihael (Documenta Praehistorica, 2014)
In this paper, we present archaeological and biochemical approaches to organic food residues, the lipids that are well preserved in ceramic matrices on prehistoric vessels. The 'archaeological biomarker revolution' concept is discussed in relation to pottery use, animal exploitation and the evolution of dietary practices in prehistory.
Keywords: ceramic; datiranje; hrana; keramika; lipidi; lončevina; neolitik; posodje; prazgodovina